Weaving Global Meaning: The Role of Language and Literature in Interpreting History - Alifaricha, Zazylah; Walida, Ziana; Samara, Arbila Dwi; Hilmiyah, Ismi Zayyina (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Amid the currents of globalization and growing uncertainty in the contemporary world, language and literature serve as powerful tools for reconstructing and reinterpreting historical narratives through a cross-cultural lens. This paper explores how literary texts and linguistic expressions not only document historical events but also reveal deeper dynamics related to power, identity, and collective memory that shape societies over time. By adopting an interdisciplinary approach—encompassing literary theory, postcolonial studies, and historical analysis—this study emphasizes that world literature, especially from postcolonial contexts and marginalized groups, offers alternative perspectives that challenge dominant historiography, which often centers on Eurocentric viewpoints. Such texts function as mediums of resistance, healing, and cultural negotiation, allowing suppressed voices to emerge and be recognized. Furthermore, the role of language—in its evolution, shifts, and politicization—demonstrates how historical narratives continue to be shaped and contested within global discourse. Through critical readings of selected literary works and reflections on linguistic phenomena, this paper argues that history is not fixed or singular, but a dynamic and pluralistic construction woven from diverse human experiences, languages, and collective imaginations. Ultimately, this study underscores the importance of broadening cultural and critical perspectives to foster empathy, understanding, and dialogue in an increasingly fragmented world.